2001
DOI: 10.1080/09658210042000012
|View full text |Cite
|
Sign up to set email alerts
|

Complexity effects in visuo-spatial working memory: Implications for the role of long-term memory

Abstract: Several studies have shown that the capacity of visuo-spatial working memory is limited by complexity. Using a variant of the Corsi blocks task, this paper investigated the effect of complexity of the to-be-remembered path on visuo-spatial memory span. Redundancy was determined by three Gestalt principles: symmetry, repetition and continuation. Experiment 1 revealed an effect of path complexity. The subsequent experiments explored whether the superiority for recall of structured over complex paths can be attri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
111
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(125 citation statements)
references
References 56 publications
(90 reference statements)
13
111
0
1
Order By: Relevance
“…The present results are in agreement with the previous findings that the capacity of WM can be expanded by chunking the stimuli on the basis of information stored in LTM (Chase & Ericsson, 1981;Chase & Simon, 1973;Craik & Lockhart, 1972;Gobet & Simon, 1998;Kemps, 2001;Miller, 1956). However, we have no direct evidence that chunking-based integration occurred in the present study.…”
Section: Discussionsupporting
confidence: 66%
“…The present results are in agreement with the previous findings that the capacity of WM can be expanded by chunking the stimuli on the basis of information stored in LTM (Chase & Ericsson, 1981;Chase & Simon, 1973;Craik & Lockhart, 1972;Gobet & Simon, 1998;Kemps, 2001;Miller, 1956). However, we have no direct evidence that chunking-based integration occurred in the present study.…”
Section: Discussionsupporting
confidence: 66%
“…These data support and largely extend the existing evidence (e.g., Jiang et al, 2000;Kemps, 2001;Peterson & Berryhill, 2013;Woodman et al, 2003;Xu & Chun, 2007) showing that Gestalt principles of perceptual organization, like the tendency to perceive and interpret environment in the simple, orderly, and regular way (Law of Pragnanz), and the influence of such attributes of perceptual objects as proximity, similarity, closure, and continuity for their grouping into coherent wholes, which are well-known to organize visual perception, influence also the active maintenance and access of information in VWM during the absence of perceptual stimulation. These results have crucial significance for our understanding of the mechanisms and function of one of the crucial elements of human mind architecture -working memory (i.e., its visual component).…”
Section: Resultssupporting
confidence: 88%
“…Kemps (2001), using the Corsi blocks test (tapping manually a set of objects from the 5 × 5 matrix in the same sequence as they were previously highlighted), has demonstrated that the recall was better when the sequence was spatially symmetrical than it was not. This result was later replicated by Rossi-Arnaud, Pierroni, and Baddeley (2006), who additionally showed that symmetry along the vertical axis was more effective than along the horizontal and diagonal axis, although all three types of symmetry increased recall as long as the target items were highlighted simultaneously (as this facilitated symmetry detection).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, the studies suggest that organizing principles are used to describe a path or trajectory across a sequence of locations. Simple or redundant paths are easier to encode and remember than less predictable ones (see, e.g., Kemps, 2001;Parmentier, Elford, & Mayberry, 2005;SchumannHengsteler, Strobl, & Zoelch, 2004). A third type of investigation has looked for grouping effects in spatial span by clustering the spatial locations and manipulating the convergence of temporal and spatial orders (see, e.g., De Lillo, 2004;Smyth & Scholey, 1994).…”
mentioning
confidence: 99%